PENGARUH PEMBERIAN Indigofera zollingeriana DALAM RANSUM TERHADAP BOBOT POTONG, BOBOT KARKAS, DAN BOBOT NONKARKAS ITIK PEKING - Meidi, Mas; Riyanti, Rr; Sutrisna, Rudy; Septinova, Dian (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
This study aimed to determine the effect of Indigofera zollingerianan on slaughter weight, carcass weight, and non carcass weight of Peking duck. This study was conducted from February through April 2018 in Integrated Laboratory Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Ducks used in this study was 2 weeks old Peking duck totaling 20 birds. This study used a completely randomized design (CRD), consisting of 5 treatments and 4 replications with treatment Indigofera zollingeriana R0: 0%; R1: 4%; R2: 8%; R3: 12%; and R4; 16%. Data were analyzed by using ANOVA with level of 5%, significantly different results in a further test using the least significant difference (LSD). The results showed that slaughter weight, carcass weight, and non carcass weight Peking duck had no significant (P> 0.05) which means that the provision of Indigofera zollingerianan 4–16% in the diet resulted in slaughter weight, carcass weight, and non carcass weight relative same. Keywords: Indigofera zollingeriana, Peking duck, Slaughter weight, Carcass weights, Non carcass weights.